2018
DOI: 10.1038/s41598-018-20957-2
|View full text |Cite
|
Sign up to set email alerts
|

Stromal C-type lectin receptor COLEC12 integrates H. pylori, PGE2-EP2/4 axis and innate immunity in gastric diseases

Abstract: Tissue stroma is known to be important in regulating Hp-mediated inflammation, but its interaction with Hp and dendritic cells (DCs) remains to be determined. To this end, the potential crosstalk between H. pylori (Hp) infected gastric stromal cells (Hp-GSCs) and DCs was investigated. Primary GSCs from cancerous and adjacent normal tissues were generated from gastric cancer patients, and monocyte-derived DCs were obtained from healthy individuals. Levels of cytokines and prostaglandin E2 (PGE2) were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…High MMP7 expression facilitated cancer invasion and angiogenesis by degrading extracellular matrix macromolecules and connective tissues in vivo. Recently, the direct interaction between this bacterial pathogen and fibroblasts has been proposed16 suggesting that H. pylori can interact with several components of connective tissue components including fibroblasts. The most virulent H. pylori strains have been shown to harbor the cag pathogenicity island encoding the type IV secretion system,3, 17 allowing the delivery of bacterial cytotoxins into gastric epithelial cells, inducing phenotypic alterations reminiscent of an epithelial to mesenchymal transition (EMT) 3, 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%
“…High MMP7 expression facilitated cancer invasion and angiogenesis by degrading extracellular matrix macromolecules and connective tissues in vivo. Recently, the direct interaction between this bacterial pathogen and fibroblasts has been proposed16 suggesting that H. pylori can interact with several components of connective tissue components including fibroblasts. The most virulent H. pylori strains have been shown to harbor the cag pathogenicity island encoding the type IV secretion system,3, 17 allowing the delivery of bacterial cytotoxins into gastric epithelial cells, inducing phenotypic alterations reminiscent of an epithelial to mesenchymal transition (EMT) 3, 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%
“…pylori-gastric stromal cells interaction and mediating crosstalk between these cells and dendritic cells (28). Finally, and particularly important for the background of this study, surface-bound CL-12 has been suggested to play a role in complement activation through the classical pathway via its association with C-reactive protein and C1q (29).…”
Section: Introductionmentioning
confidence: 78%
“…In addition, dysregulation of C4A, and GPS2, are also known to be involved in the development of leukemia in humans when they are dysregulated (30,31). The gene COLEC12 produces a receptor that mediates the crosstalk between dendritic cells and gastric stromal cells and has been associated with the development of gastric cancer patients when deregulated (32). BLV miRNAs seem to dysregulate the expression genes to proliferate in cattle.…”
Section: Discussionmentioning
confidence: 99%